Pengaruh Kegiatan Plugged dan Unplugged Terhadap Berpikir Komputasional Murid SMP - Setiawan, Yohan Adi; Ringo, Sariaman Siringo (Jurnal Didaktika Pendidikan Dasar, 2024)
Computational thinking has become a major focus in education in many countries, including Indonesia. As a foundation for developing students’ computational thinking, informatics learning can be done using unplugged and plugged methods. Students are still at the basic stage of Computational Thinking in Informatics learning. Based on several previous studies obtained conflicting results regarding the influence of plugged and unplugged methods on students’ computational thinking. The present study endeavors to assess the impact of both plugged and unplugged activities on the computational thinking proficiencies of junior high school students. This quasi-experimental research enlisted two 7th-grade cohorts comprising a cumulative total of 64 students. Each cohort, comprising 32 students, was assigned to a control group (unplugged activities) and an experimental group (plugged activities). Based on pretest and posttest tests in groups, this research reveals that both unplugged and plugged activities have a big influence on improving junior high school students’ computational thinking skills. Meanwhile, the results of the Mann-Whitney test show that there is no difference between the effect of the plugged method and the unplugged method on computational thinking skills. This research indicates that teachers can choose one of the Informatics learning methods, either plugged or unplugged, or combine the two methods.